EMULGEL : A NOVEL APPROACH TO TOPICAL DRUG DELIVERY - DADWAL MEENAKSHI (International Journal of Pharma and Bio Sciences, 2013)
Emulgel is emulsions, either of the oil-in-water or water-in-oil type, which are gelled by mixing with a gelling agent. Emulsion in gel have emerged as one of the most interesting topical drug delivery system as it has dual release control system i.e. emulsion and gel. Also the stability of emulsion is increased when it is incorporated in gel. Gels are a relatively newer class of dosage form created by entrapment of large amounts of aqueous or hydro alcoholic liquid in a network of colloidal solid particles. Gel formulations generally provide faster drug release compared with ointments and creams. In spite of many advantages of gels a major limitation is in the delivery of hydrophobic drugs. So to overcome this limitation emulgels are prepared and with their use even a hydrophobic drug can enjoy the unique properties of gels.